THE ‘WHAT’S-IN-A-NAME’ QUESTION VIEWED THROUGH THE PRISM OF INTERCULTURAL COMMUNICATION - Boyko, Lyudmila (Vertimo studijos, 2017)
As both cultural universals and ethnic markers, personal names provide a means to look at the issues of individual and cultural identity, with communicative practices in view. The paper treats personal names both as lexical units ‘in transit’ from one language (and culture) to another, and as a vulnerable constituent of the individual’s self, which requires special treatment in intercultural communication. Also addressed in the paper are some of the issues of cultural differences between the Russian and English ways of using anthroponyms, discrepancies between name formats, and current trends in name use.I am nobody! Who are you? Are you nobody, too? Then there’s a pair of us. Don’t tell – they’d banish us!Emily Dickinson